E-Marketplace Adoption of MSMEs Agro-Industry Fishery Products in Kalanganyar Village, Sidoarjo: a UTAUT Model Approach - Alivia Firda Halimatul Jannah; Eko Nurhadi; Prasmita Dian Wijayati (International Journal of Economics, Business and Innovation Research, 2024)
This study analyzes the factors influencing the adoption of e-marketplace by fishery product agro-industry MSMEs in Kalanganyar Village using the UTAUT (Unified Theory of Acceptance and Use of Technology) model. The research method used is Structural Equation Modeling with a Partial Least Square (SEM-PLS) approach, involving observations and interviews with 50 MSMEs. The results showed that Effort Expectancy and Social Influence had a positive and significant effect on Behavioral Intention, while Performance Expectancy had no significant effect. Facilitating Conditions have a positive and significant effect on e-marketplace adoption, but Behavioral Intention has no significant effect on adoption. The R-Square value shows that the variables studied affect 31.4% of Behavioral Intention and 47% of adoption. The Predictive Relevance (Q²) value of 0.6364 indicates a fairly good model. This study emphasizes the importance of the availability of information, assistance, and training to improve the utilization of e-marketplaces by MSMEs, especially for housewives who have difficulty understanding technology.